2002
DOI: 10.1074/jbc.m201770200
|View full text |Cite
|
Sign up to set email alerts
|

The Small Heat Shock Protein αB-crystallin Negatively Regulates Apoptosis during Myogenic Differentiation by Inhibiting Caspase-3 Activation

Abstract: Myoblasts respond to growth factor deprivation either by differentiating into multinucleated myotubes or by undergoing apoptosis; hence, the acquisition of apoptosis resistance by myogenic precursors is essential for their development. Here we demonstrate that the expression of the small heat shock protein ␣B-crystallin is selectively induced in C2C12 myoblasts that are resistant to differentiation-induced apoptosis, and we show that this induction occurs at an early stage in their differentiation in vitro. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
196
2
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(212 citation statements)
references
References 31 publications
10
196
2
4
Order By: Relevance
“…Previous studies 73,74 have shown that both mutants displayed decreased protection against apoptosis induced by staurosporine and other stress conditions. To explore the possible mechanisms for the decreased protection, we have created the two mutants using wild-type HaA and HaB cDNAs and PCR amplification procedure.…”
Section: Haa-and Hab-crystallins Can Interact With Bcl-x S and Bax Inmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies 73,74 have shown that both mutants displayed decreased protection against apoptosis induced by staurosporine and other stress conditions. To explore the possible mechanisms for the decreased protection, we have created the two mutants using wild-type HaA and HaB cDNAs and PCR amplification procedure.…”
Section: Haa-and Hab-crystallins Can Interact With Bcl-x S and Bax Inmentioning
confidence: 86%
“…The differential antiapoptotic mechanism was further illustrated in a recent study in which aB-crystallin but not Hsp27 was found capable of repressing differentiation-induced caspase-3 activation. 74 The results from both GST pulldown assay ( Figure 4) and coimmunoprecipication-linked Western blot analysis with antibodies against aA/B-crystallin and Bcl-X S (Figure 5a and d) suggest that HaB seems to have slightly stronger affinity to Bax and Bcl-X S than HaA does. However, this is not consistent with the coimmunoprecipitation-linked Western blot analysis with anti-Bax antibody (Figure 5c).…”
Section: Antiapoptotic Mechanisms Of A-crystallinsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is correlated with reduction in cell proliferation and mitosis inhibition . For many cell types and stressors, αB-crystallin inhibits apoptosis by preventing the auto proteolytic maturation of caspase-3 (Arrigo et al, 2002;Kamradt et al, 2002). αA-crystallin may also enhance survival by interacting with anti-apoptotic factors Bax and Bcl-xs (Liu et al, 2004).…”
Section: Cell Survival Is Correlated With Expression Of αA and αB In mentioning
confidence: 99%
“…Some sHSPs have crucial roles in neuronal apoptosis and muscle function 3,22 . R116C in αA-crystallin diminishes its protective ability against stress-induced lens epithelial cell apoptosis 23 , and αB-crystallin negatively regulates apoptosis by inhibiting caspase-3 activation 24 . HSPB2 associates specifically with and activates the myotonic dystrophy protein kinase, which causes myotonic dystrophy (OMIM 160900; ref.…”
mentioning
confidence: 99%